The Problem of Revelation and Philosophizing in Gaudiya Vedanta - D. N. Popov (Интеллект. Инновации. Инвестиции)
The research is aimed at the historical and philosophical reconstruction of the problems of Gaudiya Vedanta theory of knowledge related to philosophizing, the concept of revelation and qualification (adhīkāra), in the philosophy of India of XVI–XX centuries. Gaudiya Vedanta, the philosophy of Gaudiya Vaishnavism, is the last independent branch of Vedanta in Indian philosophy, which summarizes in its texts the problems and solutions of previous Vedanta movements in the XVI century. The specificity of this school lies in the emphasis on personalism, ethics and aesthetics. The approach of «world philosophy» (F. I. Shcherbatskoy, V. K. Shokhin, R. V. Pshu) was used for the study, according to which in the philosophy of each developed culture we can find similar philosophical problems in varying degrees of elaboration in connection with a unique historical situation. Based on this approach, a historical and philosophical reconstruction of the hermeneutics of Gaudiya Vedanta is carried out, in which philosophizing is considered as the result of the process of revelation. The historical and philosophical analysis allowed us to identify two stages of the formation of the concept of revelation (śabda, śāstra, samādhi, veda) and qualification (adhīkāra) in Gaudiya Vedanta: classical (Jiva Gosvami and Krishnadas Kaviraja, Visvanatha Chakravarti XVI–XVII centuries), modern (Bhaktivinoda, Bhaktisiddhanta, Bhaktivedanta XIX–XX centuries). The analysis of historiography shows that Gaudiya Vedanta, using the apparatus of new logic (navya-nyaya), entered the age of globalization and accepted the challenges not only of the existing tradition of Indian philosophy, but also of European philosophy. For this purpose, the school used a system of interpretation and receiving revelations both inside and outside the sacred sphere with an expanded understanding of revelation and sacredness. In addition, Gaudiya Vedanta formulated special requirements for a thinker working with revelation. These requirements were supposed to preserve the uniqueness of the school and ensure intellectual continuity. They imply the need for the philosopher to have both some academic qualification (theology of the first order): knowledge of texts, their logic of explanation, prudence and insight, and spiritual qualifications (theology of the second order): morality, detachment and, in particular, sensitivity to religious emotions in relation to God. The historical and philosophical reconstruction allowed us to explicate a special model of philosophizing of Gaudiya Vedanta, based on revelation, personalistic theology, ethics and aesthetics. The results of the research can be useful for historians of Eastern philosophy with new material, analysis of concepts, explication of the role of historical and philosophical contexts.